FAKTOR-FAKTOR PENENTU REAKSI HARGA SAHAM SEBAGAI DAMPAK PENGUMUMAN RIGHT ISSUE - Merna Surjadi (Jurnal Akuntansi Bisnis, 2017)
The objective of this research is to analyze factors explaining the stock price reaction as effect of right issue. This paper examines 49 companies where announce right issue in Jakarta Stock Exchange during June 1997 to December 1999. Dependent variable is Cumulative Abnormal Return (CAR). Price Book Value (PBV), Debt Equity Ratio (DER), ratio of amount of new equity’s share to outstanding share (RBL), and ratio of offer price to closing price one month prior to effective date (OFFER) are used as independent variable. The analysis show DER and RBL have negative coefficient which statistically significant at the 0,05 level. PBV and OFFER have statistically insignificant coefficient.Keywords: CAR, PBV, DER, RBL